THE IMPACT OF ANGKLUNG ART-BASED INTERVENTION ON THE HEALTH OF SENIOR CITIZENS IN MALAYSIA - Muhammad Asyraf, Mohd Bakri; Mohammad Kamal, Sabran; Asrenee, Ab Razak; Rosalam, Che Me; Saiful Hasley, Ramli; Muhammad Jameel, Mohamed Kamil; Siti Suhaily, Surip (University of Malaya, 2025)
This study explores the therapeutic potential of angklung a traditional bamboo musical instrument as an art-based intervention to enhance the well-being of senior citizens in Malaysia. Despite angklung being commonly played for recreational purposes in group settings, its specific health applications remain underexamined. Thus, this study aims to identify the benefits of angklung as an art-based activity for the elderly and to analyse its impact on their physical, psychological, cognitive, and social well-being. This study employed the qualitative descriptive method, and data were collected through literature review and semi-structured interviews. Participants included angklung experts, medical professionals, caregivers and elderly residents from two care centres in Penang. The Angklung Healing Art Project was used as the primary intervention. The collected data were then analysed thematically using the WHOQOL framework, and purposive sampling was employed to ensure sampling diversity. The findings revealed that angklung activities helped improve the participants’ physical and psychological health, independence, social interactions and their overall engagement in daily life. The elderly participants expressed enjoyment, increased motivation, and a sense of accomplishment after being involved in the sessions. Some also reported reduced anxiety and improved memory recall following the intervention. In this light, despite cognitive limitations faced by some of the participants, most were able to participate meaningfully, demonstrating the angklung's accessibility. The melodic and calming tones of the angklung, along with its lightweight and easy-to-play design, make it a suitable tool for therapeutic and recreational purposes in aged care environments. This study has highlighted the importance of incorporating culturally relevant, low-barrier, and enjoyable musical activities into elderly care programs. It also recommends the development of assistive tools to support angklung use among older adults with physical or cognitive limitations.